Optimal designs for experiments on two-line and four-line crosses - Parsad, Rajender; Gupta V.K.; Gupta, Sudhir (Utilitas Mathematica, 2005)
The optimality aspects of designs for 2-line and 4-line cross experiments are studied. Universally optimal designs for 1-way and 2-way elimination of heterogeneity are obtained. MS-optimality is investigated for designs with 0-way, 1-way and 2-way elimination of heterogeneity. Several methods of construction of universally optimal and MS-optimal block and row-column designs are given. Tables of optimal/efficient designs for 2-line and 4-line crosses have been prepared.